2012
DOI: 10.1590/s1806-37132012000600003
|View full text |Cite
|
Sign up to set email alerts
|

Subdiagnóstico de DPOC na atenção primária em Aparecida de Goiânia, Goiás

Abstract: Objective: To estimate the prevalence of undiagnosed COPD among individuals with risk factors for the disease treated at primary health care clinics (PHCCs) in the city of Aparecida de Goiânia, Brazil. Methods: Inclusion criteria were being ≥ 40 years of age, having a > 20 pack-year history of smoking or a > 80 hour-year history of exposure to biomass smoke, and seeking medical attention at one of the selected PHCCs. All subjects included in the study underwent spirometry for the diagnosis of COPD. Results: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
(21 reference statements)
1
15
0
5
Order By: Relevance
“…In the present study, the underdiagnosis rate was 70.0% for new COPD cases diagnosed until the end of the nine-year follow-up period and 62.3% for all of the participants in the follow-up phase of the PLATINO study. Similar rates have been reported in a study involving primary health care clinics in the city of Aparecida de Goiânia, Brazil, ( 12 ) and in cross-sectional epidemiological studies conducted in other countries, such as Spain ( 13 ) and the USA, (14)- 71.4%, 78.2%, and 74.9%, respectively-which shows that underdiagnosing COPD is not a problem observed only in developing countries. This means that spirometry is underused, a finding that has also been reported in a study conducted in Spain.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, the underdiagnosis rate was 70.0% for new COPD cases diagnosed until the end of the nine-year follow-up period and 62.3% for all of the participants in the follow-up phase of the PLATINO study. Similar rates have been reported in a study involving primary health care clinics in the city of Aparecida de Goiânia, Brazil, ( 12 ) and in cross-sectional epidemiological studies conducted in other countries, such as Spain ( 13 ) and the USA, (14)- 71.4%, 78.2%, and 74.9%, respectively-which shows that underdiagnosing COPD is not a problem observed only in developing countries. This means that spirometry is underused, a finding that has also been reported in a study conducted in Spain.…”
Section: Discussionsupporting
confidence: 84%
“…No presente estudo, o subdiagnóstico foi de 70,0% para os novos casos de DPOC diagnosticados após nove anos de seguimento e de 62,3% ao se considerar todos os indivíduos que participaram da fase de seguimento do estudo PLATINO. Taxas similares também foram reportadas em uma amostra de unidades básicas de saúde em Aparecida de Goiânia, Brasil ( 12 ) e em estudos epidemiológicos transversais realizados em outros países, como Espanha ( 13 ) e EUA ( 14 ) (71,4%, 78,2% e 74,9%, respectivamente), demonstrando que a ausência do diagnóstico de DPOC não é uma realidade somente de países em desenvolvimento. Isso reflete que a espirometria é um exame subutilizado, à semelhança do que foi encontrado em um estudo realizado na Espanha.…”
Section: Discussionunclassified
“…In a very interesting paper published recently in the Brazilian Journal of Pulmonology, Queiroz et al ( 1 ) reported a COPD underdiagnosis rate of 71.4% in a primary health care setting. In addition, the authors observed that only 5.6% of the subjects previously diagnosed with COPD had undergone pulmonary function tests (PFTs).…”
Section: To the Editormentioning
confidence: 99%
“…( 2 ) In a study evaluating patients treated at primary care clinics in the city of Aparecida de Goiânia, Brazil, 71% had never undergone spirometry and therefore had an unconfirmed diagnosis of COPD. ( 4 ) …”
Section: Introductionmentioning
confidence: 99%